2013
DOI: 10.1007/s10834-013-9368-x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Quality Among Young Couples from an Economic and Gender Perspective

Abstract: Less than a third of married couple households in the United States are composed of families with one breadwinner. This is a stark contrast to a mere 40 years ago when men were the primary breadwinner for the majority of households. The goal of this study was to determine how the perception of household chores is related to relationship quality. Specifically we wanted to determine how perception of household chores is related to relationship quality reported by partners from a traditional economic and a gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Finally, perceptions may be more important than reality in predicting relationship outcomes (Britt et al, 2017;Britt & Nazarinia Roy, 2014). If one partner perceives that materialistic attitudes and behaviors negatively influence the relationship, materialism is a problem for the couple regardless of actual behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, perceptions may be more important than reality in predicting relationship outcomes (Britt et al, 2017;Britt & Nazarinia Roy, 2014). If one partner perceives that materialistic attitudes and behaviors negatively influence the relationship, materialism is a problem for the couple regardless of actual behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…While jobs traditionally held by men have ebbed, service sector jobs have risen, prompting more women to enter the workforce to help cover family expenses (Schlosser, 2001). As of 2011, fewer than 22% of U.S. families had a traditional male-breadwinner and female-homemaker household (Britt & Roy, 2014). Meanwhile, as Americans, both male and female, increasingly work during evenings and weekends, both partners have begun role sharing at home (Presser, 2007).…”
Section: The More Progressive Positionmentioning
confidence: 99%
“…Accordingly, marital quality has improved for couples who embrace egalitarian roles-that is, where wives contribute more to family income and husbands perform a greater share of housework (Amato, Johnson, Booth, & Rogers, 2003;. Moreover, Britt and Roy (2014) reported that discrepancies in income among partners does not significantly predict marital quality.…”
Section: The More Progressive Positionmentioning
confidence: 99%
“…Money or economic factors alone are not enough to account for imbalances in relationships, as gender provides a more accurate and nuanced understanding (Britt and Roy 2013 ). Multiple studies found that as women earned more money, they still did more housework and their influence in decisions tended to not increase at the same rate as men.…”
Section: Power As Decision-making Dominancementioning
confidence: 99%